Executive Subdomains Are Differentially Associated With Psychosocial Outcomes in Major Depressive Disorder - Knight, Matthew J.; Baune, Bernhard T. (Frontiers in Psychiatry, 2018)
Background: Deficits in executive functioning are frequently associated with poor psychosocial outcomes in Major Depressive Disorder (MDD). However, there is a poor understanding of the domain-specific relationships between executive subdomains (e.g., forward planning, decision making) and specific psychosocial issues (e.g., occupational functioning, social relationships). The current study explored these relationships across currently depressed and remitted MDD patients, as well as a healthy control group. Methods: Data from 142 participants were obtained from the Cognitive Functioning and Mood Study (CoFaM-S), a cross sectional study of mood, cognition, and psychosocial functioning in mood disorders. Participants’ (current depression n= 31, remitted depression n= 52, healthy controls (HC) n= 59) executive functioning was evaluated with well-established tests of executive subdomains (i.e., Tower of London, card sorting, Stroop task). The Functioning Assessment Short Test (FAST) was employed to clinically evaluate psychosocial dysfunction. Results: The results indicated that forward planning was most strongly associated with psychosocial issues in the current depression group as compared to HCs, while cognitive updating was was primary in the remitted group vs HC. Conclusions: These findings suggest that executive subdomains are deferentially associated with psychosocial issues across different stages of depressive illness, and that forward planning and cognitive updating should be considered in adjunctive cognitive treatment.